Prevalence of Linguatula sp., a food-borne zoonotic aberrant arthropod, in river buffaloes slaughtered at Tabriz slaughterhouse, Iran. (5th November 2020) - Hajipour, Nasser; Ketzis, Jennifer; Hassanzadeh, Parviz
Abstract: Background: Canids and herbivores are the definitive and intermediate hosts of Linguatula sp., respectively. Methods: Mesenteric lymph nodes (n=32 525) were randomly collected from 7585 buffaloes from July 2016 to July 2019 and examined macroscopically. Results: Results showed that 388 (5.11%) buffaloes were infected. The intensity of infection was determined to be 3.07±0.07. Significant statistical association was identified between infection rate and age and sex. Although there were no significant differences in the infection rate over different seasons, the highest infection rate was observed in autumn. Conclusions: These data highlight the importance of inspection at slaughter.